Think globally, build locally: A technological platform for low-cost, open-source, locally-assembled programmable bricks for education - Arnan Sipitakiat (2018)
"Programmable bricks" are microcontroller-based devices that can be used in various educational projects, such as robotic prototypes, environmental sensing, and interactive art. They have been used in educational settings for many years, but particularly in developing countries their penetration has been limited due either to unavailability or prohibitive cost. In this paper, we discuss recent work on the GoGo Board, an open-source, extensible, low-cost programmable brick mainly designed for developing countries. We discuss the board's main design principles, which were based on our extensive fieldwork, as well as implication for learning activities, the use of low-cost materials, and local construction of boards. We use data and observations from studies in several countries such as Brazil, Mexico, and Thailand. Copyright 2010 ACM.